Biocompatible silver nanoparticles: An investigation into their protein binding efficacies, anti-bacterial effects and cell cytotoxicity studies - Sourav Das; Leader Langbang; Mahabul Haque; Vinay Kumar Belwal; Kripamoy Aguan; Atanu Singha Roy (Elsevier, 2021)
Green synthesis of silver nanoparticles (AgNPs) has garnered tremendous interest as conventional methods include the use and production of toxic chemicals, products, by-products and reagents. In this regard, the synthesis of AgNPs using green tea (GT) extract and two of its components, (−)-epigallocatechin gallate (EGCG) and (+)-catechin (Ct) as capping/stabilizing agents, is reported. The synthesized AgNPs showed antibacterial activity against the bacterial strains Staphylococcus aureus and Escherichia coli, along with anticancer activity against HeLa cells. After administering nanoparticles to the body, they come in contact with proteins and results in the formation of a protein corona; hence we studied the interactions of these biocompatible AgNPs with hen egg white lysozyme (HEWL) as a carrier protein. Static quenching mechanism was accountable for the quenching of HEWL fluorescence by the AgNPs. The binding constant (Kb) was found to be higher for EGCG-AgNPs ((2.309 ± 0.018) × 104 M−1) than for GT-AgNPs and Ct-AgNPs towards HEWL. EGCG-AgNPs increased the polarity near the binding site while Ct-AgNPs caused the opposite effect, but GT-AgNPs had no such observable effects. Circular dichroism studies indicated that the AgNPs had no such appreciable impact on the secondary structure of HEWL. The key findings of this research included the synthesis of AgNPs using GT extract and its constituent polyphenols, and showed significant antibacterial, anticancer and protein-binding properties. The -OH groups of the polyphenols drive the in situ capping/stabilization of the AgNPs during synthesis, which might offer new opportunities having implications for nanomedicine and nanodiagnostics.